An evaluation of the vocational skill learning program at Madrasah Aliyah Negeri of Yogyakarta Special Region - Andhika, Muhammad; Munadi, Sudji (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
This study aims to evaluate the vocational skills learning program at Madrasah Aliyah Negeri (MAN) of Yogyakarta Special Region with components that include: (1) learning plans (antecedents); (2) Implementation of learning (transactions); and (3) Learning outcomes (outcomes). This study uses a quantitative approach and a Countenance Stake evaluation model. The evaluation was carried out at MAN 1 Sleman, MAN 2 Bantul, and MAN 2 Kulon Progo from February to June 2020. The data collection instruments in this study used observation sheets, document review sheets, and questionnaires. The validity used is in the form of content validity and construct validity, while for reliability, Cronbach's Alpha and Intraclass Correlation Coefficient were used. The results show that: (1) planning (antecedents) of learning skills in MAN of Yogyakarta Special Region is in a good category with a percentage of 66.21%; (2) the implementation (transaction) of learning, the results using the observation technique reach excellent category (86.11%), and the questionnaire technique is in good category (78.49%). Meanwhile, in the implementation of the learning assessment, both document review and questionnaire techniques obtained good categories (68.35% and 75.05%); (3) the outcomes of students' final semester exams on skills learning in MAN of Yogyakarta Special Region reach 100% of passing the standard of each madrasah.